Competence of History Teachers in Managing IT-Based Interactive Learning at Zaria Nigeria - Salihu, J. J. (Universitas Negeri Semarang, 2023)
The aim of this research is to determine teachers' abilities in using IT-based interactive learning media in high school history learning in Zaria, analyze the obstacles teachers encounter in utilizing IT-based interactive learning media in history learning in Zaria, and determine the positive and negative impacts of using interactive learning media. IT-based history learning. The research subjects were history teachers and 22 students. This type of research is descriptive research with a qualitative approach. The results of this research illustrate that the ability of history teachers to use IT-based interactive learning media is quite good using the Management System for Teaching and Learning (MSTL). Teachers are skilled in utilizing information technology facilities and developing material into IT-based media products that are interesting and easy to apply in history learning. One of the positive impacts of using IT-based interactive learning media is that it makes it easier for teachers to deliver very dense history learning material. Meanwhile, one of the negative impacts is that it causes teachers to become dependent on information technology-based learning media.